Rancang Bangun Aplikasi Mobile Geotagging Kerusakan Jalan Berbasis Laporan Sosial Pada Platform Android - Muhammad Murtadho; Herman Tolle; Agi Putra Kharisma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The road infrastructure is an important element in driving economic growth and public development. Along with the increasing number of vehicle users, the need of an adequate road infrastructure is very substantial. Damaged road infrastructure can significantly hampered daily activities. On the other hand, mobile devices are also experiencing a rapid growth from year to year. Among the various mobile device platforms, Android has the largest user base in Indonesia. One implementation of the GPS and camera sensor on Android devices is geotagging technology which can embed geographical information on a digital media. Based on the aforementioned cases, the authors designed and built an application named ‘Markgo' to report damaged road. By fulfilling 8 functional requirements, the application passed validity test. Also, from the usability testing which includes 4 criteria, usefulness, ease of use, easiness to learn, and satisfaction, we obtained the average index value of 88.24%. From both test results can be concluded that ‘Markgo' functionality is in accordance with the design, can be accepted and facilitate the society to report damaged road infrastructure.